Electronically controlled optical polarization evolution in carbon nanotubes - Hernández‐Acosta, Marco Antonio; Martínez‐González, Claudia Lizbeth; Torres‐SanMiguel, Christopher René; Trejo‐Valdez, Martin; Martínez‐Gutiérrez, Hugo; Torres‐Torres, Carlos (Mathematical methods in the applied sciences, 2021)
A standard optical Kerr gate configuration assisted by electronic signals in propagation through a nonlinear optical media was analyzed. The evolution of the polarization of optical pulses induced by a polarization‐resolved two‐wave mixing experiment was modulated by the frequency of an electronic signal in carbon nanotubes. Ellipsometric evaluations revealed a refractive index of 2.4 in the samples in thin film form, while UV–vis spectroscopy measurements indicated an absorption peak close to 300‐nm wavelength. From Raman, studies were estimated 91% of single‐wall carbon nanotubes and 9% of the multiwall carbon nanotubes integrating the samples. The electrical impedance dependent on electrical frequency and optical irradiance in the nanostructures was explored by nanosecond pulses at a 532‐nm wavelength. Electrochemical impedance spectroscopy studies pointed out an inductive behavior at low electrical frequencies in contrast to a capacitive behavior for high electrical frequencies present in the nanostructures. An enhancement in magnitude of the third‐order nonlinear optical susceptibility by the assistance of a logic signal of 4 V provided a change from 7 × 10 −9 esu to 1.1 × 10 −8 esu in the samples studied. Considering the impact of the vectorial nature of light for ruling the amplitude and splitting properties of the beams, immediate applications for developing photonic and optoelectronic systems controlled by nonlinear optical phenomena can be contemplated.